Find the polynomial g(x), Mathematics

On dividing the polynomial 4x4 - 5x3 - 39x2 - 46x - 2 by the polynomial g(x) the quotient is x2 - 3x - 5 and the remainder is -5x + 8.Find the polynomial g(x). (Ans:4 x2+7x+2)

Ans:    p(x) = g (x) q (x) + r (x)

g(x) =px) - rx)/q( x)

let p(x) = 4x4 - 5x3 - 39x2 - 46x - 2 q(x) = x2 - 3x - 5 and r (x) = -5x + 8

now p(x) - r(x) = 4x4 - 5x3 - 39x2 - 41x - 10

when px) - rx)/qx)

∴ g(x) = 4x2 + 7x + 2

= 4x2 + 7x +2

Posted Date: 4/8/2013 1:53:26 AM | Location : United States







Related Discussions:- Find the polynomial g(x), Assignment Help, Ask Question on Find the polynomial g(x), Get Answer, Expert's Help, Find the polynomial g(x) Discussions

Write discussion on Find the polynomial g(x)
Your posts are moderated
Related Questions
The law of cosines can only be applied to acute triangles. Is this true or false?

In a frequency distribution mode is 7.88, mean is 8.32 find the median.  (Ans: 8.17) Ans:  Mode = 3 median - 2 mean 7.88 = 3 median - 2 x 8.32 7.88 +16.64 = 3 median

Difference Between Experiment and Outcome Experiment is an operation that produces outcomes which can be observed. Outcome/Event is the result of an experiment.

50387 divided by 21

briefly explain how the famous equation for the loss of heat in a cylindrical pipe is derived

A venn diagram is a pictorial representation of the sample space of an experiment. It is usually drawn as a rectangular figure representing the sample space and it cont

a ,b,c are complex numbers such that a/1-b=b/1-c=c-1-a=k.find the value of k

1. Consider the relation on A = {1, 2, 3, 4} with relation matrix: Assume that the rows and columns of the matrix refer to the elements of A in the order 1, 2, 3, 4. (a)

What is a scatter diagram? A scatter diagram is a graphical representation of data points for a particular sample. Choosing a dissimilar sample or enlarging the original one ca

Determine the inverse transform of each of the subsequent. (a)    F(s) = (6/s) - (1/(s - 8)) + (4 /(s -3)) (b)   H(s) = (19/(s+2)) - (1/(3s - 5))  + (7/s 2 ) (c)    F(s) =